Digital Etching of Molybdenum Interconnects Using Plasma Oxidation - Ivan Erofeev; Antony Winata Hartanto; Muhaimin Mareum Khan; Kerong Deng; Krishna Kumar; Zainul Aabdin; Weng Weei Tjiu; Mingsheng Zhang; Antoine Pacco; Harold Philipsen; Angshuman Ray Chowdhuri; Han Vinh Huynh; et al. (Advanced Materials Interfaces)
Abstract Molybdenum (Mo) has a high potential of becoming the material of choice for sub‐10 nm scale metal structures in future integrated circuits (ICs). Manufacturing at this scale requires exceptional precision and consistency, so many metal processing techniques must be reconsidered. In particular, present direct wet chemical etching methods produce anisotropic etching profiles with significant surface roughness, which can be detrimental to device performance. Here, it is shown that polycrystalline Mo nanowires can be etched uniformly using a cyclic two‐step “digital” method: the metal surface is first oxidized with isotropic oxygen plasma to form a layer of MoO3, which is then selectively removed using either wet chemical or dry isotropic plasma etching. These two steps are repeated in cycles until the intended metal recess is achieved. High uniformity of plasma oxidation defines the etching uniformity, and small metal recess per cycle (typically 1–2 nm) provides precise control over the etching depth. This method can replace wet etching where high etching precision is needed, enabling the reliable manufacturing of nanoscale metal interconnects.